2016
DOI: 10.1126/science.aaf7073
|View full text |Cite
|
Sign up to set email alerts
|

Extensive migration of young neurons into the infant human frontal lobe

Abstract: The first few months after birth, when a child begins to interact with the environment, are critical to human brain development. The human frontal lobe is important for social behavior and executive function; it has increased in size and complexity relative to other species, but the processes that have contributed to this expansion are unknown. Our studies of postmortem infant human brains revealed a collection of neurons that migrate and integrate widely into the frontal lobe during infancy. Chains of young n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
307
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 332 publications
(327 citation statements)
references
References 46 publications
16
307
3
1
Order By: Relevance
“…9). These findings are consistent with the idea that the CGE/LGE contribute substantially to late-arriving interneurons in the human frontal lobe (Paredes et al 2016). Across the human lifespan (Kang et al 2011), analysis of 11 neocortical areas revealed that SCGN expression peaks in the late mid-fetal period (GW21-GW26) and declines monotonically thereafter (Fig.…”
Section: Secretagogin Expression In Human Neocortex Is Developmentallsupporting
confidence: 78%
See 1 more Smart Citation
“…9). These findings are consistent with the idea that the CGE/LGE contribute substantially to late-arriving interneurons in the human frontal lobe (Paredes et al 2016). Across the human lifespan (Kang et al 2011), analysis of 11 neocortical areas revealed that SCGN expression peaks in the late mid-fetal period (GW21-GW26) and declines monotonically thereafter (Fig.…”
Section: Secretagogin Expression In Human Neocortex Is Developmentallsupporting
confidence: 78%
“…At birth, SCGN was widely expressed in migratory streams of young doublecortin (DCX) + neurons in the frontal lobe, including neurons comprising the Arc, a newly described caplike structure surrounding the anterior body of the lateral ventricle (Paredes et al 2016) (Supplementary Fig. 9).…”
Section: Secretagogin Expression In Human Neocortex Is Developmentallmentioning
confidence: 99%
“…13,14 By contrast, in rodents the second major site of postnatal neuronal differentiation is the OB. In the SVZ, pre-determined neuronal stem cells (NSCs) generate large amounts of NPCs.…”
Section: Car In the Neurogenic Niche Of The Svzmentioning
confidence: 99%
“…However, a substantial proportion of them is likely to be generated in the pallium from the VZ and the SVZ [12,[94][95][96] (Figure 3C). Recently, migration of subclasses of human cortical interneurons has been reported to continue after birth [97].…”
Section: Serotonin -A Chemical Messenger Between All Types Of Living mentioning
confidence: 99%
“…These interneurons expressed a combination of transcription factors and a substantial fraction of them expressed COUP-TFII or SP8 (22 or 28% respectively) that are mainly specific of 5-HT 3A + interneurons suggesting that 5-HT could also modulate the migration and positioning of these neurons in human [97]. Interestingly, in the primate cortex, it was shown that 5-HT 3A is expressed by a subset of small GABA+, substance P+ or calbindin+ neurons and by medium-size CR+ neurons [190].…”
Section: Serotonin and Neuronal Migrationmentioning
confidence: 99%